GROUND BASED MONITORING OF THE EARTH'S ENVIRONMENT AT NAGYCENK OBSERVATORY (NCK) - Bencze P.; Wesztergom V. (My University, 2007)
Ground based observations of the “Széchenyi István” Geophysical Observatory of the Hungarian Academy of Sciences (Nagycenk) offer a unique opportunity for investigation of the complex processes of Earth’s environment and of its effect on radio wave propagation. High temporal resolution recording of variations of the geomagnetic field, vertical incidence sounding of the ionosphere and observation of whistlers enable determination of plasma density profiles in the inner magnetosphere (plasmasphere) and their changes. Study of ionospheric processes and their effects in the upper atmosphere (thermosphere) is supported by a permanent GPS station. Both DC and AC fields of lightning discharges are also recorded in the Observatory. Measurement of the DC field is related to the atmospheric electric circuit, where the global thunderstorm activity is the generator and fine weather areas play the role of loading. Loading of the atmospheric electric field depends on rate of ionization, ionization being caused by galactic cosmic rays. However, galactic cosmic rays are modulated by solar activity. Similarly amplitude of Schumann resonances depend on thunderstorm activity and its distance from the recording site. Resonance frequencies occurring at wave-lengths approximating dimensions of the Earth-ionosphere waveguide are affected by conductivity variations of the upper boundary of the cavity resonator and thus, by changes of thickness of the cavity resonator.
Keywords: ATMOSPHERIC ELECTRICITY; IONOSPHERE; MAGNETOSPHERE; SCHUMANN RESONANCES; SPACE WEATHER